HOW DOES CSR STRATEGY IMPACT CORPORATE CASH POLICY IN EMERGING MARKETS? EVIDENCE FROM THE COVID-19 OUTBREAK - Polat, Ali Yavuz; Tekin, Hasan (Journal of Central Banking Law and Institutions, 2024)
This study investigates the impact of corporate social responsibility (CSR) strategy on corporate cash policy in emerging markets, with a specific focus on the COVID-19 pandemic period. By analysing data from 7,731 firm-years across 30 developing countries during the period 2002-2021, the study finds that CSR has a negative effect on cash holdings. In other words, firms with lower CSR investment tend to hold more cash. However, an interesting finding is that the negative impact of CSR on cash holdings lost its significance during the COVID-19pandemic. This suggests that during this unprecedented period of economic uncertainty and disruption caused by the pandemic, firms with higher CSR were more inclined to hoard cash as a precautionary measure. In contrast, in normal times, the dominant motive for holding cash appears to be related to agency concerns. Furthermore, the study identifies countryspecific variations in the relationship between CSR and cash holdings. For instance, firms in Brazil and Saudi Arabia tend to use cash retention as a response to higher CSR, while firms in Argentina, Malaysia, Mexico, Poland, Taiwan, and Turkiye exhibit the opposite behaviour, using higher CSR as a signal for reduced cash holdings. Additionally, the study sheds light on industry-specific differences in the relationship between CSR and cash holdings. Beverage, construction and material, industrial material, oil, gas, and coal, technology hardware and equipment, telecommunications service provider, and travel and leisure firms are more likely to use cash holdings as a substitute for CSR, while alternative energy and media firms show the opposite pattern, using higher CSR as a signal for reduced cash holdings.